The Evolution of the HVAC Industry Through the Lenses of Current Crisis - Valentin STAVER; Liliana STAVER; Larisa DODU-GUGEA (Communications of International Proceedings, 2023)
This study delves into the effects of ongoing crises, notably climate change and evolving energy policies, on the Heating, Ventilation, and Air Conditioning (HVAC) sector. Amidst a worldwide surge in awareness regarding climate issues and amplified endeavors to curb greenhouse gas emissions, the HVAC industry confronts notable challenges. However, these challenges are paralleled by considerable prospects for innovation and augmenting energy efficiency. Our research employed a hybrid methodology, intertwining secondary data examination with the analysis and synthesis of pertinent information. This included a comprehensive scrutiny of existing scientific literature and market analyses to discern both prevailing and prospective trends. The outcomes of this study reveal that climate change and energy policies exert a profound influence on the HVAC sector, catalyzing a swift progression in both technological advancements and industry practices. Moreover, our insights emphasize the necessity of enhanced cooperation between industry stakeholders and policy-makers, to position the HVAC industry at the forefront of global endeavors in mitigating climate change and enhancing energy efficiency.
Keywords: HVAC Industry; COVID-19; Climate Change; Supply Chain.